Provisions of ‘Nithar’ in Islamic Jurisprudence - El Shehab, Abeer Jassim Mohamed (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: To define Nithar, its forms, related lexicon, and its rulings and implications. Methods: The nature of the research necessitates an inductive methodology to portray jurists' differences in the juristic classification of Nithar and its provisions. In addition, the analytical methodology is employed to compare various opinions, to help in producing a balanced classification. Results: Nithar falls under the ‘enhancement purposes’ of permissible deeds. Its classification varies according to situation, the type of recipient- whether rich or poor- and the giver’s intention, with preference to its admissibility without determining the form and its permissibility without coercion, while adhering to its legal provisions concerning the giver, the given, and the recipient. Ownership of the given is established through the giver’s handover or its falling into the recipient's lap, in order to encourage convenience and alleviate difficulty. The recipient’s testimony is not dismissed but is considered according to common custom. Conclusion: This study addresses the concept of Nithar, clarifies the expression and its forms and juristic classifications, subsequent rulings, and related lexicon, ultimately establishing legal provisions for the giver, the given, and the recipient, in order to prevent harm and reap its benefits. The final section explains the implications of Nithar, how the giver’s ownership of the given terminates, and the condition attached to the recipient’s ownership. The study recommends adhering to these legal provisions to achieve the intended purpose of Nithar.